2015
DOI: 10.3390/su71115527
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Critical Factors in the Eco-Efficiency of Remanufacturing Based on the Fuzzy DEMATEL Method

Abstract: Remanufacturing can bring considerable economic and environmental benefits such as cost saving, conservation of energy and resources, and reduction of emissions. With the increasing awareness of sustainable manufacturing, remanufacturing gradually becomes the research priority. Most studies concentrate on the analysis of influencing factors, or the evaluation of the economic and environmental performance in remanufacturing, while little effort has been devoted to investigating the critical factors influencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 35 publications
0
23
0
3
Order By: Relevance
“…Designing product with reference to suitability of Operations like Disassembly, Reassembly and Cleaning is vital. However, it is observed that little effort has been put into understanding the dynamic nature of customer requirements in the Remanufacturing process design [17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Designing For Multi-life Cycle Productmentioning
confidence: 99%
“…Designing product with reference to suitability of Operations like Disassembly, Reassembly and Cleaning is vital. However, it is observed that little effort has been put into understanding the dynamic nature of customer requirements in the Remanufacturing process design [17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Designing For Multi-life Cycle Productmentioning
confidence: 99%
“…Atasu et al [1] point out that, confronted with the competition of TPRs, OEMs should engage in the remanufacturing process and use it as a marketing strategy to defend their market share through price discrimination. Ferrer and Swaminathan [12] characterize the competition between an OEM and a remanufacturer in multi-periods and indicate that the OEM's remanufactured products have a higher recognition than those from the remanufacturer in the market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To promote environmentally friendly practices for the reuse of e-products, many countries have strict regulations based on the principal of extended producer responsibility (EPR), to encourage producers to engage in recycling and reusing [7]. However, even though remanufacturing may result in a reduction in the production cost [1,4], many manufacturers are still not willing to embrace remanufacturing for fear of expensive investment in the fixed cost of remanufacturing or the internal cannibalization of the sales of new products [8]. Moreover, various uncertainties in the acquisition of products and recovery management also discourage manufacturers from entering into remanufacturing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining these strategies with the economic characteristics of China, the Chinese government presented "China manufacturing 2025" [3]. As mentioned in the above strategies, the development of the equipment manufacturing industry significantly facilitates economic growth.…”
Section: Introductionmentioning
confidence: 99%